2008
DOI: 10.1001/jama.2008.720
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Liver Transplantation Before and After Introduction of the MELD Score

Abstract: Context In February 2002, the allocation system for liver transplantation became based on the Model for End-Stage Liver Disease (MELD) score. Before MELD, black patients were more likely to die or become too sick to undergo liver transplantation compared with white patients. Little information exists regarding sex and access to liver transplantation. Objective To determine the association between race, sex, and liver transplantation following introduction of the MELD system. Design, Setting, and Patients A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
344
5
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(374 citation statements)
references
References 23 publications
20
344
5
5
Order By: Relevance
“…[7][8][9] Our finding that AA patients with HCC had poorer survival than their white counterparts is in agreement with the findings of Artinyan et al, 10 who also reported that survival differences persisted among patients who underwent LT. In contrast to Moylan et al, 12 who reported that racial disparity in the use of LT was decreasing over time, we found no significant change in racial/ethnic disparities with regard to the use of LT for HCC between 1998 and 2007. However, Moylan et al studied patients with all etiologies of endstage liver disease who were on the LT waiting list.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] Our finding that AA patients with HCC had poorer survival than their white counterparts is in agreement with the findings of Artinyan et al, 10 who also reported that survival differences persisted among patients who underwent LT. In contrast to Moylan et al, 12 who reported that racial disparity in the use of LT was decreasing over time, we found no significant change in racial/ethnic disparities with regard to the use of LT for HCC between 1998 and 2007. However, Moylan et al studied patients with all etiologies of endstage liver disease who were on the LT waiting list.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Moylan et al studied patients with all etiologies of endstage liver disease who were on the LT waiting list. 12 The current study has several potential limitations. Because we did not have the information required to calculate each patient's MELD score, we used closely related comorbidity data regarding liver disease, renal failure, coagulopathy, and other conditions, which were strong predictors of undergoing LT, although they were not as accurate as the MELD scores.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although black patients generally are under represented on transplantation waiting lists, 23,24 the subset of patients in the UNOS database who undergo transplantation represents a particularly homogenous population given the ranking methods used for patient listing, particularly in the post-MELD era. This point was reported by Moylan et al, 25 who noted that there was no correlation between race and the receipt of liver transplantation in the era of MELD scores. Our study demonstrates that, after OLT for HCC, significant racial and ethnic disparities in both graft survival and overall survival persist, with black patients again demonstrating a significant survival deficit compared with all other groups.…”
Section: Discussionmentioning
confidence: 60%
“…33,34 Incorporation of serum creatinine into the model resulted in gender disparities in receipt of transplant and higher waitlist mortality among women by 13% compared to men. 35 This is due to the fact that for the given renal function, women tend to have lower serum creatinine compared to men due to lower muscle mass in women.…”
Section: Impact On Disparities In Liver Transplantationmentioning
confidence: 99%